2010
DOI: 10.1089/scd.2009.0467
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Hematopoietic Differentiation of Mouse Embryonic Stem Cells by an AGM-Derived Stromal Cell Line is Not Further Enhanced by Overexpression of HOXB4

Abstract: Hematopoietic differentiation of embryonic stem (ES) cells can be enhanced by co-culture with stromal cells derived from hematopoietic tissues and by overexpression of the transcription factor HOXB4. In this study, we compare the hematopoietic inductive effects of stromal cell lines derived from different subregions of the embryonic aorta-gonad-mesonephros tissue with the commonly used OP9 stromal cell line and with HOXB4 activation. We show that stromal cell lines derived from the aorta and surrounding mesenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 67 publications
1
12
0
1
Order By: Relevance
“…However, our observations that ectopically expressed HOXB4 can support the development of ESC-derived HSPCs capable of engrafting immunodeficient Rag2 (Ϫ/Ϫ) ␥C (Ϫ/Ϫ) [23] and immunocompetent 129S6/SvEvTac mice long-term, without the need of any coculture with stromal cells, may support the idea of a BMP4 independence of HOXB4-expressing cells. In agreement with this, others have also observed that coculture of HOXB4-expressing ESCs with AGM-derived stromal cells also did not further enhance their hematopoietic differentiation [41]. A recently published observation by Jackson et al may explain the nonadditive effect of stromal cocultures on hematopoietic differentiation of HOXB4 ϩ -ESCs [42].…”
supporting
confidence: 62%
“…However, our observations that ectopically expressed HOXB4 can support the development of ESC-derived HSPCs capable of engrafting immunodeficient Rag2 (Ϫ/Ϫ) ␥C (Ϫ/Ϫ) [23] and immunocompetent 129S6/SvEvTac mice long-term, without the need of any coculture with stromal cells, may support the idea of a BMP4 independence of HOXB4-expressing cells. In agreement with this, others have also observed that coculture of HOXB4-expressing ESCs with AGM-derived stromal cells also did not further enhance their hematopoietic differentiation [41]. A recently published observation by Jackson et al may explain the nonadditive effect of stromal cocultures on hematopoietic differentiation of HOXB4 ϩ -ESCs [42].…”
supporting
confidence: 62%
“…The products were electrophoresed in a 1.8% agarose gel and stained with ethidium bromide. The primer sequences are shown in Table 1 (4,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) Statistical analysis Data are shown as mean ± standard deviation. Statistical analysis was performed using the two-independent samples t-test for two-group comparisons and one-way …”
Section: Polymerase Chain Reactionmentioning
confidence: 99%
“…The aberrant expression of HOXB4 is often related to poor prognoses of leukemia (23), mesothelioma (24) and ovarian cancer (25). Overexpression of HOXB4 is considered as a catalyst for the development of leukemia and influences the leukemia phenotype (26). Furthermore, Lehne et al (27) discovered that HOXB4 played an important role in chemoresistance of CML.…”
Section: Hoxb4 Knockdown Reverses Multidrug Resistance Of Human Myelomentioning
confidence: 99%